2002
DOI: 10.1038/sj.ijir.3900833
|View full text |Cite
|
Sign up to set email alerts
|

Causes of sexual decline in aging married men: Germany and America

Abstract: Married men in Germany (n ¼ 48) and America (n ¼ 50) between 50 and 80 years old, none in poor health, provided comparable information on sexual behavior and attitudes, and gave saliva samples from which testosterone was assayed. Sexuality declines with age, as expected. Neither testosterone nor psychological depression explain levels of sexuality. In both nations, wife's desire for intercourse, subject's ability to maintain an erection, and subject's imagination about other women, explain certain aspects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…On the other hand, the greater role of relational factors in older patients could be attributed, at least partly, to the age-related decrease of sexual desire of patients' partners. 24,27 In fact, we observed that sexual desire is inversely related to age in patients' partners, but not in patients themselves, as previously reported; 27 for this reason, a discrepancy between male and female sexual desire, which could disturb relationship, can be observed in many aging couples. The increased impact of relational factors in aging individuals could partly explain the observed age- Aging and pathogenesis of ED G Corona et al related, comorbidity-independent, increase in the prevalence of ED, which was previously described.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the greater role of relational factors in older patients could be attributed, at least partly, to the age-related decrease of sexual desire of patients' partners. 24,27 In fact, we observed that sexual desire is inversely related to age in patients' partners, but not in patients themselves, as previously reported; 27 for this reason, a discrepancy between male and female sexual desire, which could disturb relationship, can be observed in many aging couples. The increased impact of relational factors in aging individuals could partly explain the observed age- Aging and pathogenesis of ED G Corona et al related, comorbidity-independent, increase in the prevalence of ED, which was previously described.…”
Section: Discussionsupporting
confidence: 65%
“…[21][22][23] Another factor which could theoretically contribute to the increased prevalence of ED in the elderly is the loss of interest in the partner or the decrease in partner's sexual interest. 24 Very few studies 8,[24][25][26] analyzed the contribution of marriage and relational factors to ED in patients, and none of them investigated their age course.…”
Section: Introductionmentioning
confidence: 99%
“…Deteriorating health may also play a role (Eisenberg et al, 2010;Karraker et al, 2011). An explanation for the age effect is a decrease in hormone production (Addis et al, 2006), but also here the findings are not definite (Mazur et al, 2002). Udry et al (1982) report findings implying that female age rather than male age influences sex frequency due to age-related changes of female androgen production.…”
Section: Theoretical Frameworkmentioning
confidence: 74%
“…For example, there is a general misconception that differences in women's and men's T levels are responsible for the observed gender difference in sexual desire [reviewed in 28]. Studies examining T and sexual desire in healthy women yield mixed results [29][30][31], and studies in healthy men consistently find no evidence linking T with sexual desire [29,[32][33][34]. Complicating matters further, the different types of sexual desire (i.e., solitary versus dyadic) yield different associations with T in women [35], and contextual factors (e.g., sexual activity) strongly affect the association between T and sexual desire [31].…”
Section: Introductionmentioning
confidence: 98%